Diagnosis and therapy of Mycobacterium marinum: a single‐center 21‐year retrospective analysis. (24th August 2022) - Strobel, Katharina; Sickenberger, Christina; Schoen, Christoph; Kneitz, Hermann; Kolb‐Mäurer, Annette; Goebeler, Matthias
Summary: Background and Objectives: In Europe, infections with Mycobacterium (M.) marinum are rare. We conducted a retrospective single‐center study to assess the clinical spectrum of M. marinum infection and its diagnosis, treatment and outcome under real‐world conditions. Patients and Methods: Eighteen patients presenting with M. marinum infections between 1998 and 2018 were identified in the data warehouse of the University Hospital Würzburg and considered for detailed analysis. Results: Twelve patients reported aquatic exposure. In 16/18 cases the upper extremities were affected. No invasive infections were detected. Mean time to diagnosis was 15 weeks. Histology revealed granulomatous inflammation in 14 patients while mycobacterial cultures were positive for M. marinum in 16 cases. Most patients received antibiotic monotherapy (14/18) while combination therapy was administered in four cases. Treatment (with a median duration of 10 weeks) was successful in 13 patients. Five patients were lost to follow‐up. Conclusions: Our retrospective analysis of M. marinum infections at a German tertiary referral center revealed a considerable diagnostic delay and the relevance of microbiological culture, PCR and histology for diagnosis. Monotherapy with clarithromycin (rather than doxycycline) appeared as a reasonable treatment option while immunosuppressed or ‐compromised patients and those with extended disease received combination therapy.